CORRIGENDUM / ERRATUM / RETRACTION - CORRIGENDUM / ERRATUM / RETRACTION (TARBIYA: Journal of Education in Muslim Society, 2016)
RETRACTION TO: Mila, R., T. (2016). The Assessment of Critical Thinking Skill for Early Age Children Based on Criterion Referenced and Norm Referenced Interpretations. TARBIYA: Journal Of Education In Muslim Society, 3(1), 77-89. doi:10.15408/tjems.v3i1.339. This article has been retracted by Publisher based on the following reason: The Editor of Tarbiya Journal found the double publication in the article publishing due to article's content similarity published in TEKNOLOGI PENDIDIKAN Vol 5, No. 2 (2016) URL: http://jurnal.ppsuika.ac.id/index.php/TEK/article/view/495. Titled” THE ASSESSMENT OF CRITICAL THINKING SKILL FOR EARLY AGE CHILDREN BASED ON CRITERION REFERENCED AND NORM REFERENCED INTERPRETATIONS” with the same author who is Rodhoty Taza Mila. Based on clarification, Author of the article have admitted that she has published the same article published in TEKNOLOGI PENDIDIKAN Vol 5, No. 2 (2016). One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.